MEMBANGUN HARMONI ANTARA SAINS DAN AGAMA: STUDI PADA PEMBELAJARAN IPA DI MADRASAH IBTIDAIYAH - Khafidhoh, Laili; Milatilah, Fatiya; Najiba, Silfiya (Islamic Studies Journal for Social Transformation, 2024)
This study aims to describe the implementation of the integration of Islamic and scientific values in Natural Science (IPA) learning at the Madrasah Ibtidaiyah level. The method used in writing this article is a literature study, which aims to describe the implementation of the integration of Islamic values in science learning at the Madrasah Ibtidaiyah level. Data collection was carried out by tracing various sources of literature, such as relevant national and international scientific articles and journals, especially through academic platforms such as Google Scholar. This study uses a qualitative descriptive approach to obtain in-depth and comprehensive data. The results of the study obtained are that Madrasah Ibtidaiyah teachers can implement the integration of Islamic and scientific values in materials, methods, learning activities and learning evaluations.